2016
DOI: 10.1111/1462-2920.13181
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial metabolic effects of selected probiotics on diet‐induced obesity and insulin resistance in mice are associated with improvement of dysbiotic gut microbiota

Abstract: Alterations in gut microbiota composition and diversity were suggested to play a role in the development of obesity, a chronic subclinical inflammatory condition. We here evaluated the impact of oral consumption of a monostrain or multi-strain probiotic preparation in high-fat diet-induced obese mice. We observed a strain-specific effect and reported dissociation between the capacity of probiotics to dampen adipose tissue inflammation and to limit body weight gain. A multi-strain mixture was able to improve ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 46 publications
6
81
0
4
Order By: Relevance
“…A recent work shows opposite patterns upon mucin usage as substrate by Lactobacillus and Akkermansia (56), thereby suggesting that trophic interactions may underlie, at least in part, these opposite trends of both microorganisms. Actually, a negative effect on Akkermansia levels in the gut upon administration of a probiotic mixture was observed when Lactobacillus , but not other probiotic bacteria, were added to the mixture (57). Conversely, Akkermansia has been shown to increase the production of the antimicrobial peptide RegIIIγ by colonic epithelial cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…A recent work shows opposite patterns upon mucin usage as substrate by Lactobacillus and Akkermansia (56), thereby suggesting that trophic interactions may underlie, at least in part, these opposite trends of both microorganisms. Actually, a negative effect on Akkermansia levels in the gut upon administration of a probiotic mixture was observed when Lactobacillus , but not other probiotic bacteria, were added to the mixture (57). Conversely, Akkermansia has been shown to increase the production of the antimicrobial peptide RegIIIγ by colonic epithelial cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also conducted by others. Alard et al (2016) showed that adiposity dampens the effect of probiotics, which are linked to the improvement of dysbiotic gut microbiota. They observed that feeding a probiotic strain restores the abundance of A. muciniphila and Rikenellaceae and decreases Lactobacillaceae .…”
Section: Modulation Of Gut Microbiota By Dietary Approaches For Theramentioning
confidence: 99%
“…They observed that feeding a probiotic strain restores the abundance of A. muciniphila and Rikenellaceae and decreases Lactobacillaceae . These gut-associated alterations are linked with improvement in other pathological parameters and obesity (Alard et al, 2016). Recently, Park et al (2017) demonstrated that feeding of a probiotic strain L. plantarum HAC01 to HFD mice resulted in reduction of body weight, fat mesenteric fat, and other biomarkers associated with obesity.…”
Section: Modulation Of Gut Microbiota By Dietary Approaches For Theramentioning
confidence: 99%
“…lactis LMG P-28149 for 14 weeks (5 days/week, 5 × 10 8 CFU of each strain in PBS) increased A. muciniphila abundance in the fecal content of the high-fat-fed DIO mice by approximately 100 fold (from 10 6.5 /g feces on high-fat-fed group to 10 8.5 /g feces in high-fat plus probiotics group) (Alard et al, 2016). In this study, a significant inverse correlation was detected between the body weight gain and the abundance of A. muciniphila ( P < 0.001) which is consistent to other intervention studies (Everard et al, 2013; Shin et al, 2014).…”
Section: Supplement With Other Selected Probiotics Promoted a Mucmentioning
confidence: 99%
“…It is likely the strain of B. animalis subsp. lactis LMG P-28149 not L. rhamnosus LMG S-28148 exert such an A. muciniphila -promoting effect since the authors further conducted a 7-week feeding study on individual strains (10 9 CFU each) with the same protocol and found that the benefits of the mix probiotics was attributed to B. animalis not L. rhamnosus (Alard et al, 2016), though the mechanisms are unclear. Interestingly, previous studies showed that A. muciniphila supplementation did not change the gut microbiota profile in DIO mice and Apoe−/−mice (Li et al, 2016), suggesting that A. muciniphila does not directly interact with other gut bacteria.…”
Section: Supplement With Other Selected Probiotics Promoted a Mucmentioning
confidence: 99%